P01.14.B Visuospatial selective attention deficit after resection of right hemisphere gliomas: a multivariate lesion symptom mapping and diffusion tractography study. (5th September 2022) - Puglisi, G; Viganò, L; Sciortino, T; Leonetti, A; Rossi, M; Conti Nibali, M; Gay, L; Fornia, L; Cerri, G; Bello, L
Abstract: Background: The ability to select relevant information to current behavioural goals despite concomitant distractors (i.e. selective attention) is crucial for daily life. Despite the implication of fronto-parietal network in sustaining visuospatial selective attention has been considered crucial, the role of subcortical structures is still unclear. Aim of this study was to evaluate the impact of neurosurgical removal of right gliomas on visuospatial selective attention performances. Material and Methods: The visuospatial selective attention domain was assessed pre- and postoperatively (1 month follow-up) in 73 patients operated for right hemisphere gliomas. Support-vector-regression lesion-symptom mapping and disconnectome analysis (Lesion Quantification Toolkit, HCP 1065 data) were used to evaluate the relationship between the resection cavities and the postoperative performance on a standardized selective attention test. To test and refine the atlas-based results, in a subset of 17 patients with preoperative diffusion tractography, the postoperative outcome was correlated with the percentage of disconnection for different white matter tracts. Results: Results showed that resection of a cluster enclosing the SMA-complex and the surrounding white matter was significantly associated with a decline in visuospatial selective attention performances (p<.05). Disconnectome analysis at population level revealed that the deficit was significantly correlated with the resection of superior cortico-striatal fibres, superior thalamic radiations, corticopontine projections, callosal connections and fibres of the frontal aslant tract. Within all the cortico-subcortical terminations of these tracts, disconnection of streamlines of the SMA-complex was the most associated with selective attention deficits. Tractography in single patients confirmed the population level results and suggested that ventro-lateral resections in case of inferior frontal or insular tumours significantly disconnecting the frontal aslant tract but sparing superior projection fibres were not associated with any postoperative disturbances. Conclusion: Results show converging evidence to support a critical role for the SMA/preSMA and its projections in maintaining efficiency of attentive control. The present results reveal the importance of a fronto-medial descending connectivity in mediating the voluntary control of visuospatial selective attention. From a surgical standpoint, to avoid postoperative deficits, it seems crucial to preserve SMA projection pathways, while the disconnection of the frontal aslant tract is feasible without any postoperative decline.